Dynamic of Organic Matter, Nutrient Cycling, and PH in Soil Aggregate Particle Sizes Under Long-Term Cultivation of Camellia Oleifera - Zipei, Luo; Qi, Sun; Ndzana, Georges Martial; Lijun, Chen; Yuqi, Chen; sheng, Lu; Lichao, Wu (Journal of soil science and plant nutrition, 2024)
Camellia oleifera is intensively cultivated in subtropical areas of China, exposing soils to various threats. However, the effect of long-term cultivation of Camellia oleifera on soil properties remains unclear and needs to be elucidated to improve soil and Camelia oleifera sustainable management. This study collected soil samples from different Camellia oleifera planting ages (2, 10, and 40 years) and performed aggregate fractionation and various analyses including physico-chemical, soil organic matter chemical composition analyses and a semi-quantitative analysis of organic carbon functional groups to investigate the effect of long-term cultivation of Camellia oleifera on soil macroaggregates (< 2 mm), mesoaggregates (2-0.25 mm) and microaggregates (< 0.25 mm) formation, soil organic matter (SOM), available nitrogen (AN), available phosphorus (AP), and available potassium (AK). The aggregate particles increased with increasing Camellia oleifera planting ages. Camellia oleifera long-term cultivation did not affected the soil pH in the aggregates, but significantly ( P < 0.05) increased SOM concentration with the decrease in soil aggregate size. Similarly, Phenolics-C, ketones-C, lignins-C, and alkenes-C increased in soil aggregates with increasing cultivation time and are mainly distributed in < 0.25 mm fraction. The aromatics-C, carboxylic-C, aliphatic-C, and polysaccharides-C declined with increasing cultivation time and were mainly distributed in 2-0.25 mm and < 2 mm fraction. AN is abundantly distributed in 2-0.25 mm and its abundance increases with Camellia oleifera long-term cultivation. All soils were poor in AP and AK. Our study indicated that long-term cultivation of Camellia oleifera promoted soil aggregate formation, increased available nitrogen (AN), soil organic matter (SOM) and controlled the change of SOM chemical composition. However, our study recommended providing available phosphorus (AP) and available potassium (AK) in soil with Camellia oleifera cultivation for sustainable management.